The Effectiveness of European Active Labor Market Policy - Jochen Kluve (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2006)
Measures of Active Labor Market Policy are widely used in European countries, but despite many econometric evaluation studies no conclusive cross-country evidence exists regarding ?what program works for what target group under what (economic and institutional) circumstances??. This paper results from an extensive research project for the European Commission aimed at answering that question using a meta-analytical framework. The empirical results are surprisingly clear-cut: Rather than contextual factors such as labor market institutions or the business cycle, it is almost exclusively the program type that matters for program effectiveness. While direct employment programs in the public sector appear detrimental,wage subsidies and ?Services and Sanctions? can be effective in increasing participants? employment probability.
Keywords: J00; J68; 330; Active Labor Market Policy; Program evaluation; Meta analysis